2022
DOI: 10.1590/1982-7849rac2022210005.en
|View full text |Cite
|
Sign up to set email alerts
|

Memes as Shortcut to Consumer Culture: A Methodological Approach to Covert Collective Ideologies

Abstract: Objective: the paper proposes the methodological use of memes as a shortcut to explore consumer culture. Memes as cultural texts can reveal collective circulating ideologies that may not be accessed through regular interviews. Context: memes are cultural texts that convey easy-to-understand messages, gaining strength within social networks. Cultural texts playfully present the social context and beliefs of societies. We analyzed circulating memes during the COVID-19 pandemic about elderly consumers in Brazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…This paper by Deus et al (2022) proposes the methodological use of memes as a shortcut to explore consumer culture. The authors argue that memes as cultural texts can reveal collective circulating ideologies that may not be accessed through regular interviews.…”
Section: Memes As Shortcut To Consumer Culture: a Methodological Appr...mentioning
confidence: 99%
See 3 more Smart Citations
“…This paper by Deus et al (2022) proposes the methodological use of memes as a shortcut to explore consumer culture. The authors argue that memes as cultural texts can reveal collective circulating ideologies that may not be accessed through regular interviews.…”
Section: Memes As Shortcut To Consumer Culture: a Methodological Appr...mentioning
confidence: 99%
“…Our selected papers also reflect such willingness. Deus, Campos, and Rocha (2022) present a new method of collecting and then analyzing the recent social phenomenon of memes as a way of gaining alternative and original insights into cultural discourses. The papers by Behling, Lenzi, and Rossetto (2022) and Silva, Sauerbronn, and Thiollent (2022) explore how qualitative methods of interactive qualitative analysis (IQA) and participatory action research (PAR), used more commonly in other fields, might be applied to management, organization, and administrative studies; and Melo and Dourado (2022) offer a comprehensive review that scopes the range and nature of possible qualitative methods for investigating online social phenomena and interactions.…”
Section: Qualitative Research -A Living Lively Fieldmentioning
confidence: 99%
See 2 more Smart Citations
“…The many issues that arise in the graduate school experience for students have been well-documented, including high rates of mental health issues in the population, financial hardship, conflicts with advisors and professors, and the extreme pressures to compete for scarce post-graduate faculty and research positions (Hyun et al, 2006;Jones-White et al, 2020;Liu et al, 2019;Sverdlik et al, 2018; UC-Berkeley Graduate Assembly, 2014). However, these themes have not been explored within the setting of graduate student meme culture, which research has indicated is an important outlet for expression, protest, and support among many populations under stress (Ask & Abidin, 2018;de Deus et al, 2022;Newton et al, 2022;Ortiz et al, 2021;Zidani, 2021). This study will explore, via content analysis of seven months of original memes posted to the High-Impact PhD Memes Facebook page, what attitudes and experiences are conveyed and most highly resonate with a primarily graduate student social media audience.…”
Section: Introductionmentioning
confidence: 99%